2010
DOI: 10.1016/j.jchemneu.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Cortical M1 receptor concentration increases without a concomitant change in function in Alzheimer's disease

Abstract: Although the M 1 muscarinic receptor is a potential therapeutic target for Alzheimer's disease (AD) based on its wide spread distribution in brain and its association with learning and memory processes, whether its receptor response is altered during the onset of AD remains unclear. A novel [ 35 S] GTPγS binding/immunocapture assay was employed to evaluated changes in M 1 receptor function in cortical tissue samples harvested from people who had no cognitive impairment (NCI), mild cognitive impairment (MCI), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 72 publications
0
30
1
Order By: Relevance
“…L left, R right, Ant anterior, Pos posterior, Sup superior compared to controls, but similar in neocortical areas [36], the relative pattern could suggest a loss of M1/M4 receptors in the medial temporal and cholinergic rich basal forebrain, accompanied by either preservation or an increase in cortical M1/M4 receptor availability. These changes thus may reflect a compensatory response to maintain basocortical cholinergic function given that loss of pre-synaptic receptors usually results in compensatory up-regulation of post-synaptic receptors [35]. Alternatively, the relative preservation or increase may also be the result of a postulated bidirectional modulatory effect between beta amyloid and M1 receptors in the frontal and parietal areas [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L left, R right, Ant anterior, Pos posterior, Sup superior compared to controls, but similar in neocortical areas [36], the relative pattern could suggest a loss of M1/M4 receptors in the medial temporal and cholinergic rich basal forebrain, accompanied by either preservation or an increase in cortical M1/M4 receptor availability. These changes thus may reflect a compensatory response to maintain basocortical cholinergic function given that loss of pre-synaptic receptors usually results in compensatory up-regulation of post-synaptic receptors [35]. Alternatively, the relative preservation or increase may also be the result of a postulated bidirectional modulatory effect between beta amyloid and M1 receptors in the frontal and parietal areas [41].…”
Section: Discussionmentioning
confidence: 99%
“…Utilising selective muscarinic ligands such as 3 H-pirenzepine (M1), others reported similar binding in various cortical [5] and frontal [50] regions relative to controls, though striatal binding was significantly higher [5,40]. With 3 H-oxotremorine-M (M1), increased receptor concentrations in cortical regions were found [35]. For 3 H-AF-DX116 (M2), AD uptake was lower in frontal, temporal and hippocampal areas [5], while elevated levels of 3 H-AF-DX384 (M2/M4) in the striatum and 125 I-(R, R)-QNB (M1/M4) in the claustrum, insula and cingulate cortex were observed compared to controls [40].…”
Section: Discussionmentioning
confidence: 99%
“…35 S] binding in native tissue was performed essentially as described previously (Overk et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…30 [ 3 H]-Oxotremorine-M radioligand binding studies found M 1 mAChR expression to be elevated in the AD cortical tissue, indicative of compensatory upregulation in response to a reduction in ACh levels. It was also found that while there was no correlation between function of M 1 mAChRs and the degree of cognitive impairment, a negative correlation between M 1 mAChR functional activity and severity of neuropathology (based on post-mortem neurofibrillary tangle analysis) was observed, adding further weight to the argument for selective targeting of this receptor in the treatment of AD.…”
Section: ■ the Cholinergic Hypothesis Of Memory Dysfunctionmentioning
confidence: 99%